DESIGN FOR WET BRAKE OF AUTOMOBILE BASED ON THE REAL TIME TEMPERATURE CONTROL SYSTEM - PANG JingLi (Jixie qiangdu, 2016)
In order to solve the problems of much heat during braking process,and poor stability in high speed condition of the automobile wet brake,a new type of wet brake based on the layout of real time temperature control was proposed by analyzing the working principle of the layout scheme,a new type of wet brake model was established,finally,the feasibility of the new type wet brake was verified by the bench test method. The theoretical calculation and experimental verification show that both results are consistent basically,the brake torque fluctuation of the wet brake based on the real-time temperature control system are obviously suppressed,and the brake torque stability of the brake process is obviously improved,and the brake torque of each stage is large than the traditional wet brake; the coolant temperature of the wet brake based on the real time temperature control system can be controlled in the vicinity of 70℃,which has a positive effect on improving the performance of the automobile brake system.